THE ROLE OF ISLAMIC RELIGIOUS EDUCATION IN BUILDING STUDENT AKHLAK AT SMPN 1 BABAKANCIKAO - Imam Tabroni; Hana Ihzan Nazillah; Nunung Siti Nuraeni (Education : Jurnal Sosial Humaniora dan Pendidikan, 2022)
This study aims to determine the learning of Islamic religious education at SMPN 1 Babakancikao and also to obtain an overview of the akhlak of students at SMPN 1 Babakancikao and to find out how the role of Islamic religious education in shaping the akhlak of students at SMPN 1 Babakancikao. This research was conducted in December 20-21 at SMPN 1 Babakancikao. The approach used in this research is a quantitative approach, while the research method is descriptive correlational method. And the sampling technique is random sampling. The instrument used is a questionnaire or questionnaire, while the correlation technique used is the product moment. And as for the results found in this study that there is a less significant correlation between Islamic religious education in shaping the akhlak of students at SMPN 1 Babakancikao.